Contemporary Risk Stratification and Treatment of Chronic Myelomonocytic Leukemia. (21st April 2021) - Tremblay, Douglas; Rippel, Noa; Feld, Jonathan; El Jamal, Siraj M.; Mascarenhas, John
Abstract: : Chronic myelomonocytic leukemia (CMML) is a hematologic malignancy characterized by absolute monocytosis, one or more lineage dysplasia, and proliferative features including myeloid hyperplasia, splenomegaly, and constitutional symptoms. Because of vast clinical heterogeneity in presentation and course, risk stratification is used for a risk‐adapted treatment strategy. Numerous prognostic scoring systems exist, some of which incorporate mutational information. Treatment ranges from observation to allogeneic hematopoietic stem cell transplantation. Therapies include hydroxyurea for cytoreduction, hypomethylating agents, and the JAK1/2 inhibitor ruxolitinib to address splenomegaly and constitutional symptoms. Recently, oral decitabine with cedazuridine was approved and represents a convenient treatment option for CMML patients. Although novel therapeutics are in development for CMML, further work is needed to elucidate possible targets unique to the CMML clone. In this review, we will detail the pathophysiology, risk stratification, available treatment modalities, and novel therapies for CMML, and propose a modern treatment algorithm. Implications for Practice: Chronic myelomonocytic leukemia (CMML) is a clinically heterogenous disease, which poses significant management challenges. The diagnosis of CMML requires bone marrow biopsy and aspirate with thorough evaluation. Risk stratification and symptom assessment are essential to designing an effective treatment plan, which may include hypomethylating agents (HMAs) in intermediate or high‐risk patients. The recently approved oral decitabine/cedazuridine provides a convenient alternative to parenteral HMAs. Ruxolitinib may be effective in ameliorating proliferative symptoms and splenomegaly. Allogeneic stem cell transplantation remains the only treatment with curative potential; however, novel therapies are in clinical development which may significantly alter the therapeutic landscape of CMML. Abstract : This review describes the current pathologic understanding of chronic myelomonocytic leukemia (CMML), appraises risk factors and stratification models, details treatment options, and proposes a contemporary treatment algorithm for patients with CMML.